PECULIARITIES OF NATIONAL SECURITY OF UKRAINE IN CONDITIONS INTERNATIONAL UNCERTAINTY - Набока, А. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2021)
Aspects of national security in the modern globalized world are analyzed, methods of influencing the factors of national security are studied, special attention is paid to the role of national interests in the context of national security, the issues of «legitimization of power» and «right of rebellion» as ones of the internal destabilizing factors of national security are analyzed. The main focus is given to the information and psychological confrontation in the media and its impact on human consciousness. The necessity of struggle against external influences for stable development and strengthening of own state sovereignty is analyzed. The document «On the National Security Strategy of Ukraine» is considered as a fundamental legislation that regulates and establishes the directions of threat to Ukraine in the context of information confrontation between states. The main elements of influence and their result on European countries are studied. Recent events in Belarus and the coronavirus pandemic are forcing more attention to national security issues and threats from outside players. The main factor in preserving sovereignty is the clear formulation of one's own national interests and defending them in the international arena. Extension of Ukraine’s cooperation with the world’s leading countries (especially in the field of cyber security and military cooperation) should help strengthen interstate ties and expand interstate partnerships in the field of economy and security. The main aspects of stability and instability among modern methods of political struggle are highlighted. The study of national security involves the analysis of current world political events and processes, namely – globalization, migration, economic crisis, technological development, etc. These processes are very interconnected and, to some extent, complement each other. We can see that global political change in the world at the beginning of the ХХІst century is the foundation for a new world order.